Implementasi Strategi Pembelajaran Mind Map dalam Meningkatkan Prestasi Belajar Peserta Didik pada Mata Pelajaran Pendidikan Agama Islam di SDN 042 Sulewatang - Nurzamsinar; Helma Malini (Jurnal Ilmiah Tarbiyah Umat, 2022)
This study aims to implement the Mind Map learning strategy to improve student achievement in Islamic Religious Education subjects at SDN 042 Sulewatang. The data collection techniques carried out in this study were interviews, observation, and documentation. The strategy in Mind Map learning refers to the results of words that researchers have done and get the results that there is an increase in student learning outcomes towards the Mind Map learning process that has been implemented in SD 042 Sulaluang school. The Mind Map learning strategy can stimulate students' creativity and improve student learning achievement; this can be seen in the pleasure of being active and understanding when carrying out learning activities in groups, which has increased when taking exams.